A metodologia “maker” nas escolas estaduais de Santa Catarina: contradições e possibilidades para o ensino. - Machado, Cibeli (2024)
The school plays a fundamental role in promoting learning, connecting students to concepts, theories and practices in different ways. It is the place where students come into contact with knowledge that is important for their lives. The discipline of geography plays a crucial role in this process of acquiring knowledge, presenting us with its various contents and analyzes of transformations occurring in the world, and revealing how to prepare to face everyday life. The maker emerged as a “new industrial revolution” and began to spread at an accelerated pace around the world, conveying the idea that people can build or modify any object, through their creativity, with their own hands. This work's main objective is to investigate the historical context of the maker until its arrival in schools and analyze how the maker is used in geography classes and in the maker laboratory at the Escola de Educação Básica (EEB) Professora Zitta Flach in Chapecó (Santa Catarina), from its inauguration in 2020 until 2023. We opted for the methodological approach of exploratory research, based on theoretical references and the application of questionnaires with secondary data, due to the limited time available. The survey was aimed at students and teachers. The analysis of the results showed a positive perception regarding the maker methodology among the participants. However, we emphasize that, given the recent nature of the insertion of this approach into pedagogical practices, there is no way to definitively determine its effectiveness. For a more complete and in-depth understanding, more comprehensive and longitudinal investigations will be needed to assess the impact and implications of this methodology in the educational context.